Davi e Golias: o protagonismo do STF frente aos ataques do governo populista de Jair Messias Bolsonaro. - Viana, Janile Lima (2024)
The consolidation of democracy in several countries has been the subject of ruptures and crises over the years. Currently, this stems from the behavior of democratically elected leaders, called autocratic populists, who use the power of representation, through elections and their own methods, to restrict fundamental rights and discredit institutions. This action raises debate in the new Brazilian political order about the abuse of power to subvert democracy. Thus, populism is worrisome and needs to be studied, so that an authoritarian populist government can be identified and insights can be offered on the relevance of the counter-majoritarian function of the STF in the defense of constitutional democracy. In order to contextualize Jair Messias Bolsonaro's attacks on the STF and analyze the rhetoric used in an attempt to discredit the Court, an empirical qualitative research was carried out, using the hypothetical-deductive method, that aims to evaluate how the STF's responses were relevant in the protection of democracy and the role of the Judiciary, and what were the impacts of the demonstrations in the political and social sphere, in order to inquire to what extent it would be possible to credit the decisions of the STF with the isolated protagonism in the defense of the independence between the Powers. The data necessary to carry out the research were obtained from the doctrine, documents and official decisions and statements issued by the STF. It is concluded that the STF, although in the performance of its relevant function and assuming an institutional posture, did not play an isolated role in the defense of independence between the Powers, what happened was a collective effort of other actors who did not succumb to bolsonarists wishes.